(untitled) - Najsrova, Anna (Aura musica, 2013)
Paper reflects the current state of liturgical music at the Cathedral of the Holy Saviour in Ostrava. It focuses on activities as a church choir, local youth group and the organists who are currently active in the local parish. The paper is also a list of the most important concerts and musical performances, which in the temple of the Holy Saviour in recent years took place.
Keywords: liturgical music; Ostrava; Cathedral of the Holy Saviour